Rancang Bangun Robot Pembersih Halaman Berbasis Mikrokontroler - Remigius Tandioga; Simon Ka’ka; Muh. Maggi Ali Akbar (Politeknik Negeri Ujung Pandang, 2019)
A yard cleaning robot was made to be able to clean the yard by sucking leaves and trash particles that are 125 mm x 41 mm in size and weighing 50 grams. This robot can run straight on a flat surface. In this research, the page cleaning robot uses a microcontroller ATMega 328 (Arduino Uno) as a controller and a vacuum cleaner to suck the trash in the form of leaves. The program used in this robot uses the Arduino programming with the following working system: when the robot circuit is activated the dc motor will rotate moving the robot to run straight while using a compass sensor to detect angles and the navigator for movement of motor direction. When the robot is walking the garbage is swept and sucked by the vacuum cleaner. When there is a barrier at a distance of 50 cm in front of the robot, the robot will automatically rotate 180º using an ultrasonic sensor mounted in front of the robot that gives information to the controller.